The Milk of Dreams : Biennale Arte 2022. - Margutti, Flavia Fossa; Pietragnoli, Maddalena; Albano, Anna; Dolzani, Francesca; Gasparato, Giulia (s.l. : La Biennale di Venezia, 2022)
Blloshmi, Lumturi ; Heller, Mónica ; Arutiunian, Andrius ; Fusinato, Marco ; Knebl, Jakob Lena & Scheirl, Ashley Hans ; Akhundova, Fidan ; Baghirzade, Agdes ; Infinity ; Khankishiyeva, Sabiha ; Novruzova, Fidan (Fidam Kim) ; Saadatkhan, Ramina ; Zhuk (Israfilova, Narmin) ; enz.
Deel 1: Participating Countries and Collateral Events ; Deel 2: Exhibition
La Biennale di Venezia, Venezia, 2022
boek